2018
DOI: 10.1051/matecconf/201816302003
|View full text |Cite
|
Sign up to set email alerts
|

Failure mode in shear of steel fiber reinforced concrete beams

Abstract: Experimental tests were carried out to assess the failure model of steel fiber reinforced concrete beams. Experimental research was focused on observing changes in the behavior of the tested elements depending on the amount of shear reinforcement and the fiber. Model two-span beams with a cross-section of 80x180 mm and a length of 2000 mm were tested. The beams had varied stirrup spacing. The following amounts of steel fibres in concrete were used: 78.5 kg/m3 (1.0%) i 118 kg/m3 (1.5%). Concrete beams without f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The notations used in this database are given in the “List of notations”. For a number of references [42,44,50,52,54,59,67,69,70,71,72,73,75,76,77,78,80,81,83,84,85,88,89,94,96,97,98,99,100,102,103,104,106,107,109,110,111,112,115,116,117,118,119,123,124] information about the geometry of the support and loading plate was missing. These values were then approximated based on figures of the test setup in the original reference.…”
Section: Methodsmentioning
confidence: 99%
“…The notations used in this database are given in the “List of notations”. For a number of references [42,44,50,52,54,59,67,69,70,71,72,73,75,76,77,78,80,81,83,84,85,88,89,94,96,97,98,99,100,102,103,104,106,107,109,110,111,112,115,116,117,118,119,123,124] information about the geometry of the support and loading plate was missing. These values were then approximated based on figures of the test setup in the original reference.…”
Section: Methodsmentioning
confidence: 99%
“…The values from the drawings are used for the database. The ratio av/d reported in [116] is 2.7. For the database entries, the size of the support plate measured from the technical drawings is used, and the effective depth is calculated assuming a cover of 10 mm.…”
Section: Overview Of Shear Prediction Equationsmentioning
confidence: 91%
“…The notations used in this database are given in the "List of notations". For a number of references [42,44,49,51,53,58,66,[68][69][70][71][72][74][75][76][77]79,80,[82][83][84]87,88,93,[96][97][98][99][101][102][103]105,106,[108][109][110][111][114][115][116][117][118]122,123,126], information about the geometry of the support and loading plate was missing. These values were then approximated based on figures of the test setup in the original reference.…”
Section: Overview Of Shear Prediction Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bentz et al [16] indicated that the above also implies differences in the behavior of support zones reinforced longitudinally with FRP bars. Oller et al [17] and Kosior-Kazberuk [18] indicated that, in accordance with the superposition principle, the shear load capacity of an element loaded with transverse force is dependent on the following factors: shear reinforcement contribution, load capacity resulting from aggregate interlocking, the load capacity of concrete in the compressed zone, the dowel action of longitudinal reinforcement, and the residual tensile strength of concrete across the crack. Composite reinforcement is characterized by a much lower modulus of elasticity than steel reinforcement.…”
Section: Introductionmentioning
confidence: 93%